Solid Waste Temporary Collection Site (TPS) For the Lon Malang Beach Tourist Area, Sampang Regency - Alfiah, Taty; Sari, Dwina Aprilianing; Pramestyawati, Talent Nia (Faculty of Civil Engeneering and Planning - ITATS, 2024)
Lon Malang beach tourism is one of the tourist attractions in Sampang district, developed as a sustainable tourism area. Naturally, Malang Lon Beach has white sand, and prawn cypresses, also equipped with several facilities including photo spots suitable for social media, games for children, etc. Research data was collected through interviews, field surveys, taking and measuring samples, and laboratory analysis. The research conclusion was that visitors to Lon Malang Sampang beach tourism produced a waste generation of 563.8 kg/day with a waste generation rate of 1.41 kg/person.day or 1.41 kg/visitor.day. Lon Malang beach tourism waste is dominated by styrofoam at 36.7%, food waste at 19.3%, plastic waste at 13.5%, and coconut shells at 12.8%. The density of Lon Malang Sampang beach waste gives an average measurement result of 79.6 kg/m3, with a water content of 41% and a water content of 3.06%. The Lon Malang Beach Waste Temporary Storage Place (TPS) is proposed to have a capacity of 12 m3, in the form of 2 (two) waste containers which will be transported using arm-roll trucks with a frequency of 3 (three) times per week.